Relationship with Parents, Symptoms of Depression and Internet Addiction among Adolescents During the Pandemic Period - Solecki, Roman; Mróz, Anna (International Journal of Research in E-learning, 2024)
The research presented in this article aimed to answer the following question: what is the role of social support and quality of family relationships in the context of depressive symptoms and abuse of the Internet during the COVID-19 pandemic and remote learning among adolescents? The study was conducted among 619 adolescents aged 11-15. The survey questionnaire was constructed from standardised research tools. The study showed that 40.0% of the students had increased depressive symptoms. Heavy Internet use affected 16.0% of the respondents, including 9.2% of those who had aggravated symptoms of depression and addiction at the same time. At the same time, it was noted that girls, compared to boys, were more often found amongst adolescents experiencing symptoms of depression.Students belonging to the group with depressive and addictive symptoms experienced significantly more difficulties in their relationships with family members compared to the group without symptoms. Students showed less severity of depressive symptoms if they rated their relationship with their parents as positive. The results showed that the quality of family relationships is most important for the normal functioning of adolescents without depressive symptoms, also in a pandemic situation.